Temporal trends and epidemiology of Staphylococcus aureus surgical site infection in the Swiss surveillance network: a cohort study. Issue 2 (February 2018) - ; Balmelli, Carlo; Eisenring, Marie-Christine; Harbarth, Stephan; Kuster, Stefan P.; Marschall, Jonas; Spicher, Virginie Masserey; Pittet, Didier; Ruef, Christian; Sax, Hugo; Schlegel, Matthias; Schweiger, Alexander; et al.
Summary: Background: Staphylococcus aureus is the leading pathogen in surgical site infections (SSI). Aim: To explore trends and risk factors associated with S. aureus SSI. Methods: Risk factors for monomicrobial S. aureus SSI were identified from the Swiss multi-centre SSI surveillance system using multi-variate logistic regression. Both in-hospital and postdischarge SSI were identified using standardized definitions. Findings: Over a six-year period, data were collected on 229, 765 surgical patients, of whom 499 (0.22%) developed monomicrobial S. aureus SSI; 459 (92.0%) and 40 (8.0%) were due to meticillin-susceptible S. aureus (MSSA) and meticillin-resistant S. aureus (MRSA), respectively. There was a significant decrease in the rate of MSSA SSI ( P  = 0.007), but not in the rate of MRSA SSI ( P  = 0.70). Independent protective factors for S. aureus SSI were older age [≥75 years vs <50 years: odds ratio (OR) 0.60, 95% confidence interval (CI) 0.44–0.83], laparoscopy/minimally invasive surgery (OR 0.68, 95% CI 0.50–0.92), non-clean surgery [OR 0.78 (per increase in wound contamination class), 95% CI 0.64–0.94] and correct timing of pre-operative antibiotic prophylaxis (OR 0.80, 95% CI 0.65–0.98). Independent risk factors were male sex (OR 1.38, 95% CI 1.14–1.66), higher American Society of Anesthesiologists' score (per one-point increment: OR 1.30, 95% CI 1.13–1.51), re-operation for non-infectious reasons (OR 4.59, 95% CI 3.59–5.87) and procedure type: cardiac surgery, laminectomy, and hip or knee arthroplasty had two-to nine-fold increased odds of S. aureus SSI compared with other procedures. Conclusions: SSI due to S. aureus are decreasing and becoming rare events in Switzerland. High-risk procedures that may benefit from specific preventive measures were identified. Unfortunately, many of the independent risk factors are not easily modifiable.